ANALISIS FAKTOR YANG MEMENGARUHI KECEMASAN PADA PEGAWAI NEGERI SIPIL (PNS) DALAM UPAYA PENCEGAHAN COVID-19 DI DINAS KESEHATAN PROVINSI SUMATERA UTARA TAHUN 2021 - Rifnatul Hasanah (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2021)
Anxiety is an unclear concern felt by a person with uncertainty and helplessness feeling. Civil Servants experience anxiety in efforts to prevent Covid-19 which is caused by several factors, one of them is fear of being infected. This study is aimed to determine the most dominant factors that affect the anxiety of Civil Servants (PNS) in efforts to prevent Covid-19. This type of research was quantitative with cross sectional approach. The study population was all Civil Servants (PNS) who served in North Sumatra Provincial Health Office as many as 342 people, a sample of 117 people using a random sampling technique, using a questionnaire. Chi square test results showed that there were an effect of gender, age, education, family status, fear of infection, knowledge, development of information, history of infected coworkers, presence of people without symptoms / close contact, Rapid / Swab test in the office, prevention of infection in an office environment and social stigma against anxiety with p value <0.05. Meanwhile, health workers had no effect on anxiety with a value of p> 0.05. The results of multiple logistic regression tests showed that the most dominant factor influencing anxiety was fear of infection (OR = 60.109), history of infected coworkers (OR = 41.172), information development (35.911), and family status (0.028). It is recommended to respondents that positive lifestyle behaviors that can improve mental health well-being such as eating healthy foods, doing regular physical activity, sleeping well, getting adequate rest, and avoiding excessive social media use related to Covid-19 can have a negative impact mental health and continue to carry out and monitor the implementation of Covid-19 prevention efforts.